(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background - Musculoskeletal Disorders are one of the most leading causes of disability around the world. Rheumatoid arthritis, Osteoarthritis and Back pain are the burden over the society of disability-adjusted-life years in both the developed and developing world. The prescribed formulations from contemporary science which are available in market possess certain limitations and adverse reaction. Contra pain powder and oil are proprietary Ayurveda medicines which are indicated in acute and chronic pain management. Objective – To evaluate the Anti-inflammatory and Analgesic activities of Contra pain Lepa and Oil in Musculoskeletal Disorders. Material and methods – A cohort of 91 human subjects were included in the study and divided into four subgroups as per disease (OA, RA, spondylitis and Sprain). Contra pain lepa and Oil application was done for a period of 7 days later follow up was done on 15th and 30th day. Primary outcomes such as Pain, Tenderness, Shotha (Swelling), Stabdata (Stiffness), Range of Motion and secondary outcomes like CBC, LFT, RFT, Physician Global Assessment were performed on baseline, 7th , 15th and 30th day. Results - Significant improvement observed in Pain, Tenderness, Stiffness scoring in all groups on 7th, 15th and 30th day. No significant changes were observed in swelling in all groups on all assessment days. No significant changes were seen in the hematological values. Conclusion –Contra pain Lepa and oil topical application has proved Analgesic and anti-inflammatory activity; it is effective and safe for application.